Fundamentos teóricos de la creación de un modelo de adquisición corporativa internacional: Caso de las principales empresas de Nuevo León (Theoretical foundations for the creation of an international corporate acquisition model: Case of the main Nuevo Leon firms) - Cabeza Llanos, Luis Vicente; Blanco Jiménez, Mónica; Villalpando Cadena, Paula (Facultad de Contaduría Pública y Administración U.A.N.L., 2008)
Abstract. The importance to propose a success Model in the international corporate acquisitions consists of offering to the important Mexican firms the factors that will allow having greater success with the international investments. In this research we selected four of the most important firms of Nuevo Leon that have important experience with international acquisitions and present them the questionnaire that was designed to validate the variables of the Model. In this paper we present the theories that give the theoretical foundations to the variables of the proposed Model that consist of 6 variables or key success factors that need to be considered for an international acquisitions, which are: Country Knowledge, Industry Knowledge, Customer relationship, Supplier relationship, Technology and Market.